A real-world study on the impact of infection load on mortality in multiple myeloma patients in Finland - Anttalainen, Anna; Havula, Essi; Kysenius, Kai; Toppila, Iiro; Miettinen, Tatu; Lassenius, Mariann; Silvennoinen, Raija; Partanen, Anu; Putkonen, Mervi (SPRINGER, 2025)
Infections are a clinically significant cause of mortality in multiple myeloma (MM) patients. The high number of infections in MM patients is due to the immunosuppressive effects of the disease itself as well as treatment-related immunosuppression. In this real-world evidence (RWE) study, we used several nationwide healthcare registries of Finland to investigate the effect of infection load on mortality in MM patients during 1997-2021. The highest number of infections was recorded during the first year after MM diagnosis. In patients who received allogenic or autologous stem cell transplantation (ASCT), the number of infections during the first two years post diagnosis was significantly higher than in those treated without ASCT. When compared to their age-, sex-, and region-matched controls, MM patients accrued more infections during the year prior to diagnosis. Intriguingly, patients under 70 years old had significantly more infections already 3 years before diagnosis when compared to their matched controls. Prior to MM diagnosis, the relative proportion of streptococcal septicaemia and pneumonia due to Streptococcus pneumoniae increased the most. Of note, even one recorded infection prior to diagnosis was associated with significantly shorter median overall survival. Importantly, Cox proportional hazard models show that recorded infections both before and after diagnosis increase the independent risk of mortality in MM patients.